Novel racemosin B derivatives as new therapeutic agents for aggressive breast cancer. Issue 23 (15th December 2018) - Xiao, Xiao; Xu, Mei; Yang, Chao; Yao, Yao; Liang, Li-na; ED Chung, Philip; Long, Qun; Zacksenhaus, Eldad; He, Zhixu; Liu, Sheng; Ben-David, Yaacov
Graphic abstract: Highlights: New analogues of racemosin B were prepared and examined for anticancer activity. The derivatives showed strong anti-cancer activity against breast cancer cells. A compound induced apoptosis and inhibited autophagy, leading to G2/M arrest. Abstract: Carbazole derivatives show anti-cancer activity and are of great interest for drug development. In this study, we synthesized and analyzed several new alkylamide derivatives of racemocin B, a natural indolo[3, 2- a ]carbazole molecule originally isolated from the green alga Caulerpa racemose. Several alkylamide derivatives were found to exhibit moderate to strong growth inhibition against human breast cancer cell lines. They induced G2/M cell cycle arrest and apoptosis in the aggressive triple-negative breast cancer cell line MDA-MB-231. Among these derivatives, compound25 with the lowest IC50 induced cell death by suppressing autophagy. This was accompanied by inhibition of autophagic flux and accumulation of autophagy protein 1 light chain 3, LC3II, and p62. The novel alkylamide derivative offers a potential new treatment for human breast cancer.